Pengaruh Perbandingan Terigu dan Tepung Suweg Termodifikasi terhadap Karakteristik Mi Kering - Andi Krishna Putra, I Kadek Dwi; Diah Puspawati, Gusti Ayu Kadek; Timur Ina, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 2 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i02.p11, 2023)
Dried noodles are a type of noodle usually made from wheat flour. This research aimed to determine the effect of comparison wheat flour with modified elephant foot yam flour on characteristics of dried noodles and to determine best ratio of wheat flour and modified elephant foot yam flour produce dried noodles with the best characteristics. The experimental design used was Randomized Block Design with the comparison treatment of wheat flour and modified elephant foot yam flour which consist of 6 levels ratio: 100%:0%, 90%:10%, 80%:20%, 70%:30%, 60%:40%, and 50%:50%. Each treatment was repeated three times to obtain 18 experimental units. The data obtained were then analyzed by the Analysis of Variance and if the treatment had a significant effect, it was continued with the Duncan Multiple Range Test. The result show that comparison of wheat flour and modified elephant foot yam flour had a significant effect on moisture content, ash content, protein content, elasticity, water absorption, cooking loss, color (scoring test) and texture (scoring test). The comparison of 60% wheat flour and 40% modified elephant foot yam flour had the best characteristic of dried noodles with 7.66% of moisture content, 2.04% of ash content, 7.83% of protein content, 10.70% of elasticity, 246.43% of water absorption, 13.07 % of cooking loss, preferred color brown was slightly liked, aroma was slightly liked, preferred texture slightly chewy was slightly liked, taste was slightly liked and overall acceptance was slightly liked.